2003
DOI: 10.1074/jbc.m213265200
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase Iε Enhances the Binding of Dvl-1 to Frat-1 and Is Essential for Wnt-3a-induced Accumulation of β-Catenin

Abstract: We demonstrate that Dvl-1, casein kinase I epsilon (CKI epsilon), and Frat-1 activate the Wnt signaling pathway cooperatively. The amino acid region 228-250 of Dvl-1 was necessary for its binding to Frat-1, and the interaction of Dvl-1 with Frat-1 was enhanced by CKI epsilon. Coexpression of Dvl-1 and Frat-1 caused accumulation of beta-catenin synergistically in L cells. Both proteins also activated the transcriptional activity of T-cell factor-4 (Tcf-4) synergistically in human embryonic kidney 293 cells, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 43 publications
(64 reference statements)
6
113
1
Order By: Relevance
“…Among the diverse signal transduction pathways mediated by Dvls, regulation of small GTPase activity and following rearrangement of actin cytoskeleton is one of the most important cellular processes, including development, neurite retraction (Kishida et al, 2004), cell motility, migration (Endo et al, 2005), etc. As it has been reported that several kinases for the phosphorylation of the Dvl family are involved in response to ligand stimulation (Hino et al, 2003;Kinoshita et al, 2003; , we screened a possible candidate kinase(s) by treating a variety of kinase inhibitors, and found that the treatment of CK1-specific inhibitor, D4476, effectively suppressed the phosphorylation of Dvl2 and Dvl3. Involvement of CK1 in the Wnt-related signaling pathway has been implicated recently; CK1 enhances Wnt-3a-induced activation of the b-catenin signaling through Dvl-1 and Frat-1 binding (Hino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the diverse signal transduction pathways mediated by Dvls, regulation of small GTPase activity and following rearrangement of actin cytoskeleton is one of the most important cellular processes, including development, neurite retraction (Kishida et al, 2004), cell motility, migration (Endo et al, 2005), etc. As it has been reported that several kinases for the phosphorylation of the Dvl family are involved in response to ligand stimulation (Hino et al, 2003;Kinoshita et al, 2003; , we screened a possible candidate kinase(s) by treating a variety of kinase inhibitors, and found that the treatment of CK1-specific inhibitor, D4476, effectively suppressed the phosphorylation of Dvl2 and Dvl3. Involvement of CK1 in the Wnt-related signaling pathway has been implicated recently; CK1 enhances Wnt-3a-induced activation of the b-catenin signaling through Dvl-1 and Frat-1 binding (Hino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As it has been reported that several kinases for the phosphorylation of the Dvl family are involved in response to ligand stimulation (Hino et al, 2003;Kinoshita et al, 2003; , we screened a possible candidate kinase(s) by treating a variety of kinase inhibitors, and found that the treatment of CK1-specific inhibitor, D4476, effectively suppressed the phosphorylation of Dvl2 and Dvl3. Involvement of CK1 in the Wnt-related signaling pathway has been implicated recently; CK1 enhances Wnt-3a-induced activation of the b-catenin signaling through Dvl-1 and Frat-1 binding (Hino et al, 2003). In addition, CK1 inhibitor, D4476, blocked the differentiation of primary dopaminergic neuronal precursor cells (Bryja et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works indicate that Wnt-induced phosphorylation of Dvl (p-Dvl) and LRP6 at Ser 1490 (p-LRP6 (S1490)) initiates the Wnt/b-catenin pathway; moreover, Dvl is an important component that controls Wnt-induced LRP6 phosphorylation at Ser 1490 (Hino et al, 2003;Cong and Schweizer LVarmus 2004;Davidson et al, 2005;Zeng et al, 2005Zeng et al, , 2008Klimowski et al, 2006;Bilic et al, 2007). Through its binding to Dvl, WWOX could repress Wnt-induced Dvl and/or LRP6 phosphorylation, thereby inhibiting the Wnt/b-catenin pathway activity.…”
Section: Binding Domainsmentioning
confidence: 99%
“…Plasmid construction pCGN/GSK-3b (WT), pCGN/GSK-3bK85M, pCGN/GSK3b K85R , pCGN/GSK-3b 216F , pCGN/GSK-3b S9A and pRSETC/ GSK-3b were constructed as previously described Hino et al, 2003). Standard recombinant DNA techniques were used to construct the following plasmids: pEF-BOS-Myc/Aurora-A, pET42a( þ )/Aurora-A, pEGFPC1/ AIP, pEGFPC1/AIP S72/76A , pEGFPC1/AIP T150A , pEGFPC1/ AIP T191A and pMalC2/AIP.…”
Section: Materials and Chemicalsmentioning
confidence: 99%